SOLVING CELLULAR MANUFACTURING SYSTEM PROBLEM WITH OPERATOR ASSIGNMENT VIA METAHEURISTICS - Muangwai, Alongkorn; Kkammuang, Kwanniti (Life Sciences and Environment Journal, 2017)
Cellular manufacturing system (CMS) is an efficient approach for implementing the principles of Group Technology in a manufacturing environment. In this paper, we suggest met heuristics solution approach that Genetic Algorithm (GA) to solve this problem (small, medium and large problems). The objectives of the research are to minimize total inter-cell movement cost, intra-cell movement cost movement cost, operating cost, purchasing machinery and, salary cost. Computational results are presented by solving three problems.